2019
DOI: 10.1021/acs.estlett.9b00479
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Transcriptome Sequencing of Epidermal Mucus as a Novel Method for Oil Exposure Assessment in Juvenile Mahi-Mahi (Coryphaena hippurus)

Abstract: Crude oil-derived polycyclic aromatic hydrocarbons (PAHs) are pervasive environmental pollutants with well-established detrimental effects on the health of marine organisms. Following large-scale oil spills in the marine environment, there is a critical need for noninvasive sampling methods to assess environmental exposure to PAHs without further perturbations to the population and for long-term monitoring following a spill. To test the efficacy of epidermal mucus mRNA as a source for noninvasive sampling, juv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…In the present study, ΣPAC levels within surface waters were relatively low at the period of sampling (approximately 0.067 μg/L) and a greater cyp1a response would likely be expected at higher concentrations observed during a spill. Our results are consistent with findings of a previous study in which cyp1a1 and cyp1b1 were the top upregulated transcript in mucus of mahi-mahi following exposure to Deepwater Horizon slick oil (16.55 μg/L ΣPAC) (Greer et al, 2019). In the present study, there was a clear trend of cyp1a3 upregulation which was confirmed by qPCR at relatively low environmental concentrations and confirms that this may be a sensitive biomarker even within mucus of animals.…”
Section: Identification Of Biomarkerssupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, ΣPAC levels within surface waters were relatively low at the period of sampling (approximately 0.067 μg/L) and a greater cyp1a response would likely be expected at higher concentrations observed during a spill. Our results are consistent with findings of a previous study in which cyp1a1 and cyp1b1 were the top upregulated transcript in mucus of mahi-mahi following exposure to Deepwater Horizon slick oil (16.55 μg/L ΣPAC) (Greer et al, 2019). In the present study, there was a clear trend of cyp1a3 upregulation which was confirmed by qPCR at relatively low environmental concentrations and confirms that this may be a sensitive biomarker even within mucus of animals.…”
Section: Identification Of Biomarkerssupporting
confidence: 93%
“…In fish, molecular analysis of epidermal mucus may be a viable tool for monitoring effects of oil exposure as it is nonlethal, rapid, inexpensive, and sample procurement requires little training. Following exposure to Deepwater Horizon slick oil, RNA sequencing of mucus from juvenile mahi-mahi (Coryphaena hippurus) identified molecular changes in mucus associated with oil toxicity, such as upregulation of cytochrome P450 1A (CYP1A) and dysregulation of transcripts associated with cardiotoxicity and immunosuppression (Greer et al, 2019). Moreover, exposure of dusky splitfin (Goodea gracilis) to crude oil resulted in increased antioxidant defense response in the epidermal mucus (Dzul-Caamal et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the efficiency and accuracy of risk assessment, the adverse outcome pathway (AOP) has been applied as an important tool based on pathways and mechanistic insights. , Within the AOP framework, each adverse health effect starts with molecular initiating events (MIEs), in terms of the interactions between the contaminants and biomacromolecules such as DNA and protein, which trigger subsequent key events (KEs) toward an adverse outcome (AO). , However, several challenges are involved in MIE identification, including the difficulty in determining target biomacromolecules and characterizing their interactions with contaminants. Transcriptome analysis has emerged as a useful approach for identifying the key toxicity targets and mechanisms in risk assessment. Various contaminant-induced transcriptome patterns can help identify the biological processes and pathways associated with the toxicities at the organ or organism levels, providing critical information about potential target biomacromolecules. Molecular modeling has also been used to decipher molecular recognition and conformational changes to characterize the MIEs. The combination of in silico and in vitro assays can further establish the link between molecular alterations and toxic effects to realize the connection between MIE and KEs.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 They have provided important insights into anthropogenic impacts on aquatic food webs 6 and the response of model organisms to chemical exposures. 7 At Environmental Science & Technology (ES&T) and Environmental Science & Technology Letters (ES&T Letters), we receive large numbers of papers utilizing nucleic-acid sequencing tools, but these papers do not always effectively address research questions or evaluate hypotheses. Most such manuscripts are rejected without sending them out for peer review, and many of those sent out for peer review do not attract favorable comments and are also rejected.…”
mentioning
confidence: 99%